Contraventions: editorials from new left review - Watkins, Susan (London Verso, 2023)
This volume brings together a selection of New Left Review's writings, covering capitalist boom and bust, American hegemony, revolts from below, the rise of China, and Russia's invasion of Ukraine. Bookended by surveys of the broader political-intellectual conjuncture in which the journal is publishing, they examine both the ideologies and on-the-ground operations of liberal-imperial rule, as well as tracking counter-movements from the street to the ballot box. Included are political interventions from Perry Anderson, Tariq Ali, Mike Davis, Susan Watkins, Alexander Cockburn, Peter Gowan, Tony Wood, JoAnn Wypijewski, Tom Hazeldine and Dylan Riley
Keywords: Editorials; Right and left (Political science); Socialism